Oral Anticoagulants With Dual Antiplatelet Therapy Versus Clopidogrel in Patients After Percutaneous Coronary Intervention: A Meta-Analysis. (January 2019) - Palla, Mohan; Briasoulis, Alexandros; Kondur, Ashok
Abstract : Background: In patients on oral anticoagulation (OAC), dual antiplatelet therapy (DAPT) is often indicated after percutaneous coronary intervention (PCI). Areas of Uncertainty: We sought to investigate the effects of triple antithrombotic therapy (TT) versus dual therapy (DT) with OAC and clopidogrel on all-cause mortality, cardiovascular death, major bleeding, myocardial infarction (MI), stroke, and stent thrombosis. Data Sources: We systematically searched on MEDLINE, EMBASE, and CENTRAL for randomized controlled or cohort studies, which investigated the comparative effects of TT versus DT. We performed a meta-analysis of 6 studies (1 randomized control study and 5 cohort studies). Results: The included studies enrolled 7259 patients; 4630 (63.8%) were on TT and 2629 (36.2%) were on DT. The average follow-up time was 1.4 years. No significant differences were found between TT and DT in all-cause mortality ( P = 0.70; I 2 = 64%), stent thrombosis ( P = 0.41), myocardial infarction ( P = 0.43; I 2 = 0%), stroke ( P = 0.36; I 2 = 0%), and major bleeding ( P = 0.43; I 2 = 0%). Conclusions: In patients who are on OAC with vitamin K antagonist and underwent percutaneous coronary intervention, no significant differences were found in mortality, ischemic, and hemorrhagic complications between the patients treated with TT and DT. Thus, tailored treatment based on individual thromboembolic and bleeding risk might be the most reasonable approach in these patients.